(untitled) (Annals of Medical Research, 2021)
Aim: Systemic steroids are used when necessary in the treatment of acute asthma attacks, but they have a high potential for side effects. The role of nebulized steroids in acute asthma attacks is controversial and there are few studies on the subject. In our study, it was aimed to evaluate the efficacy of nebulized budesonide treatment in children presenting with acute asthma attack.Materials and Methods: In this study, patients aged 5-18 years who presented to emergency service with a mild acute asthma attack were evaluated. Patients with mild acute asthma attack who did not respond to nebulized salbutamol treatment at 3 doses (0.15 mg/kg/dose) administered within the first hour, were included in the study. The patients were randomly divided into two groups. Group A received single-dose systemic steroid (1mg/kg) while Group B received single-dose nebulized budesonide (500µg). The groups were compared in terms of demographics, % O2 saturation, pulmonary index score (PIS), and duration of hospital stay. Results: A total of 61 cases were enrolled to the study (Group A n=33, Group B n=28). There was no statistically significant difference between groups in terms of mean age and gender (P>0.05). In both groups, % O2 saturation values at 4th hour of treatment increased and PIS regressed significantly compared to the baseline values (P0.001). It was also found that the % O2 saturation values at 4th hour were higher in patients treated with nebulized budesonide compared to patients treated with systemic steroids (p:0.02). There was no statistically significant difference between the groups in terms of duration of hospital stay (P>0.05). Conclusion: Based on the results of our study, a single dose (500µg) of nebulized budesonide was shown to be as effective as systemic steroid therapy in the treatment of mild acute asthma attacks.